Infection control during filoviral hemorrhagic fever outbreaks - N Raabe Vanessa; Borchert Matthias (Journal of Global Infectious Diseases, 2012)
Breaking the human-to-human transmission cycle remains the cornerstone of infection control during filoviral (Ebola and Marburg) hemorrhagic fever outbreaks. This requires effective identification and isolation of cases, timely contact tracing and monitoring, proper usage of barrier personal protection gear by health workers, and safely conducted burials. Solely implementing these measures is insufficient for infection control; control efforts must be culturally sensitive and conducted in a transparent manner to promote the necessary trust between the community and infection control team in order to succeed. This article provides a review of the literature on infection control during filoviral hemorrhagic fever outbreaks focusing on outbreaks in a developing setting and lessons learned from previous outbreaks. The primary search database used to review the literature was PUBMED, the National Library of Medicine website.